Los obstáculos epistemológicos - Barrantes Campos, Hugo (2008)
We describe the concept of the epistemological obstacle, developed by G. Brousseau. We analyze the objectives of mathematical instruction: the relevance of the epistemological obstacles, its epistemology and its relationship with the theory of didactical situations.